YAP and MRTF-A, transcriptional co-activators of RhoA-mediated gene expression, are critical for glioblastoma tumorigenicity. Issue 41 (11th October 2018) - Yu, Olivia; Benitez, Jorge; Plouffe, Steven; Ryback, Daniel; Klein, Andrea; Smith, Jeff; Greenbaum, Jason; Delatte, Benjamin; Rao, Anjana; Guan, Kun-Liang; Furnari, Frank; Chaim, Olga; et al.
Abstract The role of YAP (Yes-associated protein 1) and MRTF-A (myocardin-related transcription factor A), two transcriptional co-activators regulated downstream of GPCRs (G protein-coupled receptors) and RhoA, in the growth of glioblastoma cells and in vivo glioblastoma multiforme (GBM) tumor development was explored using human glioblastoma cell lines and tumor-initiating cells derived from patient-derived xenografts (PDX). Knockdown of these co-activators in GSC-23 PDX cells using short hairpin RNA significantly attenuated in vitro self-renewal capability assessed by limiting dilution, oncogene expression, and neurosphere formation. Orthotopic xenografts of the MRTF-A and YAP knockdown PDX cells formed significantly smaller tumors and were of lower morbidity than wild-type cells. In vitro studies used PDX and 1321N1 glioblastoma cells to examine functional responses to sphingosine 1-phosphate (S1P), a GPCR agonist that activates RhoA signaling, demonstrated that YAP signaling was required for cell migration and invasion, whereas MRTF-A was required for cell adhesion; both YAP and MRTF-A were required for proliferation. Gene expression analysis by RNA-sequencing of S1P-treated MRTF-A or YAP knockout cells identified 44 genes that were induced through RhoA and highly dependent on YAP, MRTF-A, or both. Knockdown ofF3 (tissue factor (TF)), a target gene regulated selectively through YAP, blocked cell invasion and migration, whereas knockdown ofHBEGF (heparin-binding epidermal growth factor-like growth factor), a gene selectively induced through MRTF-A, prevented cell adhesion in response to S1P. Proliferation was sensitive to knockdown of target genes regulated through either or both YAP and MRTF-A. Expression of TF and HBEGF was also selectively decreased in tumors from PDX cells lacking YAP or MRTF-A, indicating that these transcriptional pathways are regulated in preclinical GBM models and suggesting that their activation through GPCRs and RhoA contributes to growth and maintenance of human GBM.